Patient trajectories in a Norwegian unit of municipal emergency beds - Heidi Nilsen; Steinar Hunskaar; Sabine Ruths (Taylor & Francis Group, 2017)
Objective: The Coordination reform was implemented in Norway from 2012, aiming at seamless patient trajectories. All municipalities are required to establish emergency care beds (MEBs) to avoid unnecessary hospital admissions. We aimed to examine occupancy rate, patient characteristics, diagnoses and discharge level of municipal care in a small MEB unit. Design: Cross-sectional, observational study. Setting: A two-bed emergency care unit. Subjects: All patients admitted to the unit during one year. Main outcome measures: Patients' age and gender, comorbidity, main diagnoses and municipal care level on admission and discharge, diagnostic and therapeutic initiatives, occupancy rate. Results: Sixty admissions were registered, with total bed occupancy 194 days, and an occupancy rate of 0.27. The patients (median age 83 years, 57% women) had mostly infections, musculoskeletal symptoms or undefined conditions. Some 48% of the stays exceeded three days and 43% of the patients were subsequently transferred to nursing homes or hospitals. Conclusion: Occupancy rate was low. Patient selection was not according to national standards, and stays were longer. Many patients were transferred to nursing homes, indicating that the unit was an intermediate pathway or a short cut to institutional care. It is unclear whether the unit avoided hospital admissions.